Bifunctional NiGa Layered Double Hydroxide for the Aerobic Oxidation/ Condensation Tandem Reaction between Aromatic Alcohols and Active Methylene Compounds. Issue 11 (9th August 2017) - Zhou, Weiyou; Zhai, Shaoyan; Pan, Jiugao; Cui, Aijun; Qian, Junfeng; He, Mingyang; Xu, Zhixiang; Chen, Qun
Abstract: A bifunctional heterogeneous catalyst based on the easily produced and economic NiGa layered double hydroxide has been developed for the aerobic oxidation/condensation tandem reactions between aromatic alcohols and active methylene compounds. Good tolerance for varied alcohols and nucleophiles has been observed. Control experiments verified the bifunctional role in the tandem reaction. The protocol could open up new perspectives in the rational design of efficient bifunctional catalytic systems. Abstract : Two‐layer cake : A bifunctional heterogeneous catalyst based on NiGa layered double hydroxide has been developed for the aerobic oxidation/condensation tandem reactions between aromatic alcohols and active methylene compounds. Good tolerance for various alcohols and nucleophiles has been observed.